Pen‐Based Writing: Recent Advances in Pen‐Based Writing Electronics and their Emerging Applications (Adv. Funct. Mater. 2/2016). (January 2016) - Li, Zedong; Liu, Hao; Ouyang, Cheng; Hong Wee, Wei; Cui, Xingye; Jian Lu, Tian; Pingguan‐Murphy, Belinda; Li, Fei; Xu, Feng
Abstract : Due to the emerging demand for methods of fabricating electronics in a cost‐effective, easily accessible way that allows for rapid prototyping way, novel techniques to design and manufacture electronics are required. On page 165, F. Li, F. Xu, and co‐workers review the recent innovations allowing ubiquitously available pens to be employed to directly write electronics, as inspired by the daily act of hand writing.